World human neutrophil antigens investigation survey - Bayat, Behnaz; Lowack, Jonas; Audrain, Marie; Croisille, Laure; Curtis, Brian; Dangerfield, Rebecca; Esmaeili, Behnaz; Grabowski, Claudia; Keller, Margaret; Kim, Hyungsuk; Kroll, Hartmut; Kvanka, Marjeta Macek; et al. (My University, 2023)
Background and Objectives: Human neutrophil antigens (HNAs) are categorized into five systems: HNA-1 to HNA-5. Given the importance of neutrophils in immunity, we sought to create awareness of the role of HNA diagnostic services in managing immune neutropenia and transfusion-related acute lung injury. To provide health communities all around the world with access to these services, we conducted a survey to create a directory of these HNA diagnostic services. Materials and Methods: An Excel table-based survey was created to capture information on the laboratory’s location and was emailed to 55 individuals with known or possible HNA investigation activity. The collected data were then summarized and analysed. Results: Of contacted laboratories, the surveys were returned from 23 (38.2%) laboratories; 17 have already established HNA diagnostic (of them 12 were regular participants of the International Granulocyte Immunobiology Workshop [ISBT-IGIW]), 4 laboratories were in the process of establishing their HNA investigation and the remaining 2 responder laboratories, did not conduct HNA investigations. In established laboratories, investigation for autoimmune neutropenia (infancies and adults) was the most frequently requested, and antibodies against HNA-1a and HNA-1b were the most commonly detected. Conclusion: The directory of survey respondents provides a resource for health professionals wanting to access HNA diagnostic services. The present study offers a comprehensive picture of HNA diagnostics (typing and serology), identifying weak points and areas for improvement for the first time. Identifying more laboratories involved in HNA diagnostics with limited access to international societies in the field will globally improve HNA diagnostics.
Keywords: alloantibody; autoantibody; autoimmune; HNA; neutropenia; neutrophil; TRALI; ddc:610